1994
DOI: 10.1091/mbc.5.8.877
|View full text |Cite
|
Sign up to set email alerts
|

Budding and fission yeast casein kinase I isoforms have dual-specificity protein kinase activity.

Abstract: We have examined the activity and substrate specificity of the Saccharomyces cerevisiae Hrr25p and the Schizosaccharomyces pombe Hhpl, Hhp2, and Ckil protein kinase isoforms. These four gene products are isotypes of casein kinase I (CKI), and the sequence of these protein kinases predicts that they are protein serine/threonine kinases. However, each of these four protein kinases, when expressed in Escherichia coli in an active form, was recognized by anti-phosphotyrosine antibodies. Phosphoamino acid analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 45 publications
(51 reference statements)
3
71
1
1
Order By: Relevance
“…Initial velocity measurements were carried out in duplicate under these conditions with ATP (4,8,16,20,26,and 37.5 tiM) as the varied substrate. Kinetic constants and their standard errors were calculated as by Hoekstra et al (1994). For assay of inhibitor potency, [y-32P]ATP was held constant (10 1.sM) and the inhibitor CKI7 (Chijiwa et al, 1989) was varied (2,4, 8, 16, and 32 1.tM).…”
Section: Phosphotransferase Assaysmentioning
confidence: 99%
“…Initial velocity measurements were carried out in duplicate under these conditions with ATP (4,8,16,20,26,and 37.5 tiM) as the varied substrate. Kinetic constants and their standard errors were calculated as by Hoekstra et al (1994). For assay of inhibitor potency, [y-32P]ATP was held constant (10 1.sM) and the inhibitor CKI7 (Chijiwa et al, 1989) was varied (2,4, 8, 16, and 32 1.tM).…”
Section: Phosphotransferase Assaysmentioning
confidence: 99%
“…A CK1-related kinase in yeast, hrr25, is essential for DNA repair and can be complemented by its mammalian homologs CK1d and e isoforms (Hoekstra et al, 1994). p53 is a substrate for both isoforms, linking them to DNA repair and cell-cycle regulation also in mammalian cells (Knippschild et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence that links CKI to the process of cell division is provided by the immunocytological studies that localized CK1 to centrosomes and cytosol vesicles during interphase but to kinetochores and mitotic spindles during mitosis (Brockman et al, 1992). A possible negative regulation by phosphorylation of the carboxyl end of the larger isoforms of yeast (Hoekstra et al, 1994) and mammals (Graves and Roach,195)s) has been reported. Developmental regulation of the expression and possible activation by y radiation of an a isoform isolated from Drosophila has also been recently described (Santos et al, 1996).…”
mentioning
confidence: 97%
“…In Saccharomyces cerevisiae, and in S. pombe, four different genes have been described and studied (Hoekstra et al, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation